Population-Based Prevalence of Myotonic Dystrophy Type 1 Using Genetic Analysis of Statewide Blood Screening Program. (16th February 2021) - Johnson, Nicholas E.; Butterfield, Russell J.; Mayne, Katie; Newcomb, Tara; Imburgia, Carina; Dunn, Diane; Duval, Brett; Feldkamp, Marcia L.; Weiss, Robert B.
Abstract : Objective: To determine whether the genetic prevalence of the CTG expansion in the DMPK gene associated with myotonic dystrophy type 1 (DM1) in an unbiased cohort is higher than previously reported population estimates, ranging from 5 to 20 per 100, 000 individuals. Methods: This study used a cross-sectional cohort of deidentified dried blood spots from the newborn screening program in the state of New York, taken from consecutive births from 2013 to 2014. Blood spots were screened for the CTG repeat expansion in the DMPK gene using triplet-repeat primed PCR and melt curve analysis. Melt curve morphology was assessed by 4 blinded reviewers to identify samples with possible CTG expansion. Expansion of the CTG repeat was validated by PCR fragment sizing using capillary electrophoresis for samples classified as positive or premutation to confirm the result. Prevalence was calculated as the number of samples with CTG repeat size ≥50 repeats compared to the overall cohort. Results: Of 50, 382 consecutive births, there were 24 with a CTG repeat expansion ≥50, consistent with a diagnosis of DM1. This represents a significantly higher DM1 prevalence of 4.76 per 10, 000 births (95% confidence interval 2.86–6.67) or 1 in every 2, 100 births. There were an additional 96 samples (19.1 per 10, 000 or 1 in 525 births) with a CTG expansion in the DMPK gene in the premutation range (CTG)35–49 . Conclusion: The prevalence of individuals with CTG repeat expansions in DMPK is up to 5 times higher than previous reported estimates. This suggests that DM1, with multisystemic manifestations, is likely underdiagnosed in practice.